PENGARUH PERMAINAN KARTU TOSS TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Anggeriani, Ade Astri; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know the effect of toss card game towards children’s age 4-5 years math ability. The research is conducted in TK Pembina 3 Pekanbaru from March to April 2017. This is pretest and posttest group design an experimental research with 30 children as samples. Type of instrument used in this study is the observation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the game toss card is influence on math ability to children aged 4-5 years in TK Negeri pembina 3 Pekanbaru City. Retrieved tcount at 5,332 with sig 0000, because sig <0.05 then we can conclude that there are influence on math abilities is significant between class with toss card game and without toss card game. Hypothesis testing can be seen at tcount= 5,332> t table = 2,048 it has been suggested that there is a significant influence in results between the control class and experiment class. The toss card card had a significant effect towards children’s age 4-5 years old math ability, at 56,41%. This is known from the different results math ability on control class and expriment class with given the toss card game treatment.Keywords: Math Ability, Toss Card